2014
DOI: 10.1007/s11356-014-3061-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in innovative mesophilic/thermophilic temperature-phased anaerobic digestion of sludge

Abstract: Anaerobic digestion (AD) is one of the few sustainable technologies that both produce energy and treat waste streams. Driven by a complex and diverse community of microbes, AD may be affected by different factors, many of which also influence the composition and activity of the microbial community. In this study, the biodiversity of microbial populations in innovative mesophilic/thermophilic temperature-phased AD of sludge was evaluated by means of fluorescence in situ hybridization (FISH). The increase of dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…The biomass at 45 °C was slightly lower in terms of diversity and richness than that of the sludge . However, the values of Chao1 and Shannon indices were higher for the 45 °C digester than the data reported previously . The rarefaction curves of all the observed OTUs persistently increased with the number of sequences and reached a plateau, demonstrating that the number of sequences was high enough to cover the diverse microbial species in each sample.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The biomass at 45 °C was slightly lower in terms of diversity and richness than that of the sludge . However, the values of Chao1 and Shannon indices were higher for the 45 °C digester than the data reported previously . The rarefaction curves of all the observed OTUs persistently increased with the number of sequences and reached a plateau, demonstrating that the number of sequences was high enough to cover the diverse microbial species in each sample.…”
Section: Discussionmentioning
confidence: 49%
“…48 digester than the data reported previously. 49,50 The rarefaction curves of all the observed OTUs persistently increased with the number of sequences and reached a plateau, demonstrating that the number of sequences was high enough to cover the diverse microbial species in each sample. The biomass retrieved at 45 ∘ C was the steepest, reflecting the highest species richness among the samples [ Fig.…”
Section: Bacterial Community Composition and Diversitymentioning
confidence: 96%
“…Regarding the total number of species/OTUs, the calculation of the Shannon Index showed that the biodiversity (H′) of the archaeal community was lower compared with bacterial biodiversity in biogas reactors ( Table S2 ). This result is in line with other studies (Fernandez et al ., 1999 ; Bengelsdorf et al ., 2013 ; Gagliano et al ., 2015 ). Differences in feedstock mixtures did not affect the biodiversity notably as indicated by similar values for H′.…”
Section: Discussionmentioning
confidence: 99%
“…The literature covers the influence of thermophilic aerobic pre-degradation Pervin et al 2013), ultrasound pre-treatment (Braguglia et al 2012;Gagliano et al 2015a), ozonation (Kobayashi et al 2009) and thermal, alkaline or combined pre-treatment (Gagliano et al 2015b;Sun et al 2014). How to influence the digester for improved performance is a question of great value, and increased knowledge of the biogas-producing microbiota and the linkage with alteration in substrate characteristics withholds promising potential for further bioengineering innovations, allowing for process development and optimisation.…”
Section: Introductionmentioning
confidence: 99%